Learning about climate change solutions in the IPCC and beyond. Issue 77 (November 2017) - Minx, Jan C.; Callaghan, Max; Lamb, William F.; Garard, Jennifer; Edenhofer, Ottmar
Highlights: Exponential publication growth threatens IPCC meeting its own mandate. Conducting climate change assessments has become a big literature challenge. Big data tools are required for conducting IPCC assessments. Organization of social science research hinders knowledge accumulation on solutions. Systematic review practices must be firmly established in IPCC and social sciences. Abstract: There has been much debate about the assessment process of the Intergovernmental Panel on Climate Change (IPCC). Yet two of the most fundamental challenges that directly threaten the ability of the IPCC to fulfill its mandate have been largely neglected so far. Firstly, the magnitude and rapid expansion of the climate change literature makes it increasingly impossible for the IPCC to conduct comprehensive and transparent assessments without major innovations in assessment practices and tools. Secondly, the structure, organization and scientific practices across the social sciences and humanities prohibit systematic learning on climate change solutions and increasingly limit the policy-relevance of IPCC assessments. We highlight the need for responses along three avenues to prepare the IPCC for continued success in the future: 1) IPCC assessments must make better use of big-data methods and available computational power to assess the growing body of literature and ensure comprehensiveness; 2) systematic review practices need to be enshrined into IPCC procedures to ensure adequate focus and transparency in its assessments; 3) a synthetic research culture needs to be established in the social sciences and humanities in order to foster knowledge accumulation and learning on climate solutions in the future. As policymakers become more interested in understanding solutions, the future prospects of global environmental assessment enterprises will depend heavily on a successful transformation within the social sciences and humanities towards systematic knowledge generation. This article is part of a special issue on solution-oriented Global Environmental Assessments.